Colonic Mucosal Epigenome and Microbiome Development in Children and Adolescents - R. Alan Harris; Rajesh Shah; Emily B. Hollister; Rune Rose Tronstad; Nils Hovdenak; Reka Szigeti; James Versalovic; Richard Kellermayer (Journal of Immunology Research)
Epigenetic and microbiome changes during pediatric development have been implicated as important elements in the developmental origins of inflammatory bowel diseases (IBDs) including Crohn’s disease (CD) and ulcerative colitis (UC), which are linked to early onset colorectal cancer (CRC). Colonic mucosal samples from 22 control children between 3.5 and 17.5 years of age were studied by Infinium HumanMethylation450 BeadChips and, in 10 cases, by 454 pyrosequencing of the bacterial 16S rRNA gene. Intercalating age-specific DNA methylation and microbiome changes were identified, which may have significant translational relevance in the developmental origins of IBD and CRC.